2007
DOI: 10.1099/vir.0.82679-0
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of two novel cutaneous human papillomaviruses, HPV93 and HPV96

Abstract: Two novel human papillomaviruses (HPVs), HPV93 and HPV96, with genomes of 7450 and 7438 bp, respectively, are described. The L1 open reading frame of HPV93 showed highest identity to HPV24 (79 %) and that of HPV96 had highest identity to HPV92 (71 %). Real-time PCR for HPV92, 93 and 96 on stripped biopsies from tumours and healthy skin from 269 immunocompetent patients found HPV DNA in 2.6 % of tumours and in 0.4 % of healthy skin samples. Double infections were observed in two tumours. HPV92 was detected in f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
27
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 34 publications
2
27
0
Order By: Relevance
“…HPV is known to be very commonly present in SCC but usually in very low amounts of virus (38)(39)(40). This is in line with our findings that MDA commonly amplifies S. aureus but only occasionally (a single tumor) amplifies HPV in SCC specimens.…”
Section: Discussionsupporting
confidence: 81%
“…HPV is known to be very commonly present in SCC but usually in very low amounts of virus (38)(39)(40). This is in line with our findings that MDA commonly amplifies S. aureus but only occasionally (a single tumor) amplifies HPV in SCC specimens.…”
Section: Discussionsupporting
confidence: 81%
“…Recently cloned types 92, 93, 94, 95 and 96 were isolated from skin lesions and belong to the cutaneous Beta Papillomavirus genus which has a less important influence on human health. [2][3][4][5] It was thus unusual that 2 independent research teams nearly simultaneously cloned and sequenced a novel HPV type that infects the anogenital mucosa, results that were presented by both groups at the 23rd International Papillomavirus Conference and Clinical Workshop 2006 in Prague. 6,7 We were greatly interested in the following article by Chen et al which was published on line March 9, 2007 in this journal 8 , on molecular characterization of HPV97 isolate cloned from a healthy Costa Rican women.…”
Section: Dear Sirmentioning
confidence: 99%
“…Several subsequent studies attempted to associate specific HPV types with the aetiology of non-melanoma skin cancer in immunosuppressed and immunocompetent patients (Shamanin et al, 1994(Shamanin et al, , 1996 Berkhout et al, 1995Berkhout et al, , 2000de Villiers et al, 1997;Forslund et al, 1999Forslund et al, , 2003bForslund et al, , 2007Asgari et al, 2008;Harwood et al, 2000Harwood et al, , 2004, whereas others demonstrated the presence of HPV in and on normal skin (Astori et al, 1998;Antonsson et al, 2000;Hazard et al, 2007;Chen et al, 2008). These studies all resulted in the identification of a vast spectrum of additional putative novel HPV types in the form of PCRamplified partial open reading frame (ORF) L1 sequences (Shamanin et al, 1996;de Villiers et al, 1997; Astori et al, 1998;Antonsson et al, 2000;Forslund et al, 2003a;.Full-length genomes of a relatively small number of these HPV isolates have been cloned and characterized (Delius et al, 1998;Forslund et al, 2003a;Vasiljevic et al, 2007Vasiljevic et al, , 2008. Definition of a papillomavirus type requires the isolation and characterization of a full-length genome in order to verify the genome organization characteristic of papillomaviruses (de Villiers et al, 2004a).…”
mentioning
confidence: 99%
“…Full-length genomes of a relatively small number of these HPV isolates have been cloned and characterized (Delius et al, 1998;Forslund et al, 2003a;Vasiljevic et al, 2007Vasiljevic et al, , 2008. Definition of a papillomavirus type requires the isolation and characterization of a full-length genome in order to verify the genome organization characteristic of papillomaviruses (de Villiers et al, 2004a).…”
mentioning
confidence: 99%